Determining if active learning through a formative assessment process translates to better performance in summative assessment. Issue 9 (1st September 2016) - Grosas, Aidan Bradley; Raju, Shiwani Rani; Schuett, Burkhardt Siegfried; Chuck, Jo-Anne; Millar, Thomas James
Abstract : Formative assessment used in a level 2 unit, Immunology, gave outcomes that were both surprising and applicable across disciplines. Four formative tests were given and reviewed during class time. The students' attitudes to formative assessment were evaluated using questionnaires and its effectiveness in closing the gap was measured by the students' final exam performance. Despite general enthusiasm for formative tests, the final exam performances were disappointing. Lessons learnt indicated that the students answered questions with 'knowledge dumps' rather than addressing the verb, and that feedback from the instructors, although providing answers, did not empower students to understand the verb in the question. Therefore, using formative tests to identify and address bad habits, rather than providing exam practice, would be a more judicious approach to formative testing and likely to improve the overall skills base of students commensurate with higher learning.